Technologies for information management of life cycle inventories of the product and service supply chain in the Brazilian industry - Reis, Everson Andrade dos [UNESP]; Costa Santos, Placida Leopoldina V. A. da [UNESP]; Chen, J.; Cuzzocrea, A.; Yang, L. T. (Ieee, 2013)
Information dissemination by means of computer networks uses information systems to store, retrieve and transmit knowledge, which are considered very important tools for society nowadays. The concepts of Information Science, their application to the solution of real situations regarding life cycle inventory and the procedures used in Information Technology provide a new direction to Information Science. This article presents an approach regarding life cycle inventories in Brazil and aspects for the concept of information management that gives support to the initiatives of life cycle assessment (LCA) methodology, contributing to the competitiveness of Brazilian industries in a globalized world.
Keywords: Information Management; Life Cycle Inventory; Sustainable Development